A multi‐institutional comparison of mitoxantrone, etoposide, and cytarabine vs high‐dose cytarabine and mitoxantrone therapy for patients with relapsed or refractory acute myeloid leukemia. Issue 8 (8th May 2020) - Christian, Sonia; Arain, Saad; Patel, Pritesh; Khan, Irum; Calip, Gregory S.; Agrawal, Vaibhav; Sweiss, Karen; Griffin, Shawn; Cahill, Kirk; Konig, Heiko; Esen, Aysenur; Shergill, Ardaman; et al.
Abstract: Relapsed or refractory acute myeloid leukemia (R/R AML) has a poor prognosis and is best treated with salvage chemotherapy as a bridge to allogeneic stem cell transplant (alloSCT). However, the optimal salvage therapy remains unknown. Here we compared two salvage regimens; mitoxantrone, etoposide, and cytarabine (MEC) and mitoxantrone and high‐dose Ara‐C (Ara‐C couplets). We analyzed 155 patients treated at three academic institutions between 1998 and 2017; 87 patients received MEC and 68 received Ara‐C couplets. The primary endpoint was overall response (OR). Secondary endpoints included progression‐free survival (PFS), overall survival (OS), duration of hospitalization, hematologic and nonhematologic toxicities, and success in proceeding to alloSCT. Baseline characteristics of the cohorts were well matched, though patients receiving Ara‐C couplets had more co‐morbidities (48.5% vs 33%; P = .07). OR was achieved in 43.7% of MEC and 54.4% of Ara‐C couplets patients ( P = .10). Ara‐C couplets patients also trended towards a longer OS and PFS, more frequently proceeded to alloSCT (31% vs 54.4%; P = .003), and experienced less febrile neutropenia (94% vs 72%; P < .001) and grade 3/4 gastrointestinal toxicities (17.2% vs 2.94%; P = .005). No significant differences in other toxicities or median duration of hospitalization were noted. This is the first multi‐institutional study directly comparing these regimens in a racially diverse population of R/R AML patients. Although these regimens have equivalent efficacy in terms of achieving OR, Ara‐C couplets use is associated with significant reductions in toxicities, suggesting it should be used more frequently in these patients.